Kadar Gula Reduksi dan Daya Terima pada Snack Bar Tinggi Energi Berbahan Dasar Tempe dan Kacang Merah untuk Atlet - Rashida Farellia Az-Zahra; Pramudya Kurnia; Fitriana Mustikaningrum (Yayasan Literasi Sains Indonesia, 2025)
Snack bars are an energy-rich food choice and can be a useful substitute for athletes to meet energy needs between main meals. As an effort to innovate food products and improve nutrition, a comparison of tempeh and red beans was conducted in making snack bars. The purpose of this study was to determine the reducing sugar content and acceptability of snack bars made from tempeh and red beans. This type of research is an experimental study with a Completely Randomized Design (CRD), namely snack bars with a ratio of tempeh and red beans Formula A (85g:65g), B (75g:75g), and C (65g:85g). Testing of reducing sugar levels was analyzed using One Way Anova followed by the LSD test. Data collection of the acceptability test used an acceptability test form involving 30 panelists and was analyzed using the Kruskal Wallis test. The results showed the highest reducing sugar content in the ratio of tempeh and red beans (75g:75g) which was 26.67% and the lowest in the ratio of tempeh and red beans (85g:65g) which was 21.78%. The results of the snack bar acceptability test showed significant differences in texture parameters between Formula A and Formula B, Formula A and Formula C snack bars (p<0.05), while there were no differences in color, aroma, taste, texture, and overall parameters (p>0.05). There was an effect of the ratio of tempeh and red beans on the reducing sugar content and texture acceptability of the snack bar.